Correction: Single nucleotide detection using bilayer MoS2 nanopores with high efficiency. Issue 23 (14th April 2021) - Sen, Payel; Gupta, Manisha
Abstract : Correction for 'Single nucleotide detection using bilayer MoS2 nanopores with high efficiency' by Payel Sen et al., RSC Adv., 2021, 11, 6114–6123. DOI: ; 10.1039/D0RA10222A .